Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.bbih.2021.100262
|View full text |Cite
|
Sign up to set email alerts
|

Strain and sex differences in somatosensation and sociability during experimental autoimmune encephalomyelitis

Abstract: Multiple Sclerosis (MS) is an immune-mediated disease that results in major locomotor deficits. However, recent studies have revealed that fatigue, slow processing speed, and memory impairment are the top variables impacting employment status for MS patients. These suggest that cognitive effects may have a greater impact on productivity, lifestyle, and quality of life than do disease-related motor deficits. However, these debilitating non-locomotive effects have been largely overlooked in rodent models of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…The C57BL/6 model of EAE generates a characteristic acute monophasic profile and stable chronic disease course ( Berard et al, 2010 ). However, despite the clear female-biased differences in MS incidence and outcome, the C57BL/6 females' preponderance in EAE susceptibility is still controversial ( Hoghooghi et al, 2020 ; Ondek et al, 2021 ; Papenfuss et al, 2004 ). In the present study, we observed a sexual dimorphism in C57BL/6 mice with respect to disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The C57BL/6 model of EAE generates a characteristic acute monophasic profile and stable chronic disease course ( Berard et al, 2010 ). However, despite the clear female-biased differences in MS incidence and outcome, the C57BL/6 females' preponderance in EAE susceptibility is still controversial ( Hoghooghi et al, 2020 ; Ondek et al, 2021 ; Papenfuss et al, 2004 ). In the present study, we observed a sexual dimorphism in C57BL/6 mice with respect to disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The C57BL/6 model of EAE generates a characteristic acute monophasic profile and stable chronic disease course (Berard et al, 2010). However, despite the clear female-biased differences in MS incidence and outcome, the C57BL/6 females’ preponderance in EAE susceptibility is still controversial (Hoghooghi et al, 2020; Ondek, Nasirishargh, Dayton, Nuño, & Cruz-Orengo, 2021; Papenfuss et al, 2004). In the present study, we observed a sexual dimorphism in C57BL/6 mice with respect to disease outcomes.…”
Section: Discussionmentioning
confidence: 99%